PENANAMAN JIWA NASIONALISME GUNA MENGHADAPI KERUSAKAN TATANAN BAHASA DAN BUDAYA LOKAL DI ERA GLOBALISASI - Angesti Ardelia Insani (Prodi PPkn Universitas Slamet Riyadi, 2022)
Today the world has faced the era of globalization, where we can exchange news and communicatewith each other effectively through today's technological innovations. However, this world ofglobalization has resulted in the younger generation entering and leading to various problems inthis country, such as a reduced sense of love for one's own language and culture at a young age.Indonesian culture may disappear over time, because Indonesian people do not want to be out ofdate with foreign cultures. As the next generation, we should have the principle of participating topreserve and strengthen our cultural defense as Indonesian people. We should focus on learning theIndonesian language and the various cultures that exist, so that our love for our own culture cangrow and develop. Our current struggle is to return the love for the homeland to the younggeneration of Indonesia.